An examination of targeted gene neighborhoods in strawberry - Davis, Thomas M. (2010)
Strawberry (Fragaria spp.) is the familiar name of a group of economically important crop plants and wild relatives that also represent an emerging system for the study of gene and genome evolution. Its small stature, rapid seed-to-seed cycle, transformability and minuscule basic genome make strawberry an attractive system to study processes related to plant physiology, development and crop production; yet it lacks substantial genomics-level resources. This report addresses this deficiency by characterizing 0.71 Mbp of gene space from a diploid species (F. vesca). The twenty large genomic tracks (30-52 kb) captured as fosmid inserts comprise gene regions with roles in flowering, disease resistance, and metabolism. A detailed description of the studied regions reveals 131 Blastx-supported gene sites and eight additional EST-supported gene sites. Only 15 genes have complete EST coverage, enabling gene modelling, while 76 lack EST support. Instances of microcolinearity with Arabidopsis thaliana were identified in twelve inserts. A relatively high portion (25%) of targeted genes were found in unanticipated tandem duplications. The effectiveness of six FGENESH training models was assessed via comparisons among ab initio predictions and homology-based gene and start/stop codon identifications. Fourteen transposable-element-related sequences and 158 simple sequence repeat loci were delineated. Conclusions: This report details the structure and content of targeted regions of the strawberry genome. The data indicate that the strawberry genome is gene-dense, with an average of one protein-encoding gene or pseudogene per 5.9 kb. Current overall EST coverage is sparse. The unexpected gene duplications and their differential patterns of EST support suggest possible subfunctionalization or pseudogenization of these sequences. This report provides a high-resolution depiction of targeted gene neighborhoods that will aid whole-genome sequence assembly, provide valuable tools for plant breeders and advance the understanding of strawberry genome evolution.